Looking for PeripheRurality - Beatrice Camaioni; Roberto Esposti; Antonello Lobianco; Francesco Pagliacci; Franco Sotte (WWWforEurope, 2013)
Rural areas still play a major role within the EU, as Europe is still a fairly rural continent. Moreover, EU rural areas are going through greater challenges and major transformations. After the Eastern enlargements of the EU (in 2004 and 2007), they are getting more and more heterogeneous, in terms of their main socio-economic features as well as of agricultural activities. According to this increasing heterogeneity, the traditional urban-rural divide can be now considered almost outdated (OECD, 2006). Indeed, a multidimensional approach is crucial in order to catch all the different features affecting trends and development of rural areas. For example, central rural regions in Continental countries sharply differ from more peripheral rural areas still facing major development issues. This research has highlighted the main dimensions affecting EU rural areas. First, some considerations on the main drivers of EU territorial development have been analysed. Then, throughout cluster analysis, specific typologies of EU rural areas have been identified. According to this classification, clear territorial patterns emerge. Actually, clusters of more central and more accessible regions are quite different from those clusters composed by more peripheral and lagging behind regions. Thus, geography still affects deeply both the economic performance of regions and their main socio-demographic trends (both in urban and rural areas). Moreover, by computing a comprehensive PeripheRurality (PR) Index, the existence of a more complex geography at the EU scale emerges. National approaches to rural and peripheral areas should be substituted by broader approaches, encompassing all the different territorial level of the analysis.
Keywords: O18; R11; R58; Q01; 330; Economic growth path; EU integration; rural development; regional policy